Islamic-Based Group Counseling towards the Realization of a Sakinah Family: Mentoring for Mothers in the Family Empowerment and Welfare Program of Puti Bungsu, Nagari Tabek - Ira Oktarini; Yanti Elvita (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2026)
The family serves as a fundamental pillar in building a harmonious and prosperous society. However, modern challenges such as economic pressures, permissive social environments, and a lack of religious understanding often hinder the creation of a sakinah family (a family characterized by tranquility, love, and mercy). This community service initiative aims to enhance the understanding and skills of the "Puti Bungsu" PKK (Family Welfare Empowerment) women in Nagari Tabek regarding the construction of harmonious families grounded in Islamic values, utilizing a group counseling approach. The project employed Participatory Action Research (PAR) with a qualitative-participatory methodology, involving 20–30 participants in a series of lectures, interactive discussions, and group counseling sessions. The results indicate an improvement in participants' understanding of the sakinah family concept, the importance of effective communication, and strategies for resolving domestic conflicts in a positive, faith-based manner. Participants demonstrated enthusiasm and active engagement, particularly during experience-sharing sessions. Group counseling proved effective in providing emotional and social support for participants as they navigate family challenges. The initiative recommends the implementation of ongoing mentoring programs covering in-depth topics such as child-rearing, family mental health, and spiritual strengthening to support the realization of.